Budidaya Pisang â€œCendevis Fhia 17â€ Untuk Pemanfaatan Lahan Kosong dan Mengangkat Perekonomian Masyarakat Di Desa Kuala Enok Indragiri Hilir Riau - Drajat Sulistiyono; Makarius Bajari (JURPIKAT (Jurnal Pengabdian Kepada Masyarakat), 2021)
"Cendevis fhia 17" banana development for the utilization of empty land in the town of Kuala Enok, is planned to work on the economy, information, just as abilities, particularly the utilization of empty grounds which are still so broad in the town of Kuala Enok are as yet not developed and used appropriately. the town is public land that is still wide spread out, Pisang cendevis through 17 is certainly not a unique imported banana, nearby Indonesian bananas have toughness, perfect, yellow, splendid, and the cost is very costly in the Riau territory region. Planted on ranches with a huge space of â€‹â€‹land without treatment, the banana seeds are sickness safe, exceptionally gainful for the body, this organic product has a great deal of healthful substance, specifically riboflavin, manganese, nutrient A, nutrient B6, niacin, fiber, protein, nutrient C, iron. , potassium, folate and magnesium, by taking a gander at a portion of these wholesome viewpoints, obviously "candevis through 17" bananas can make the body better and forestall irresistible and inside illnesses. What's more, it can lift the nearby local area's economy